ESTIMATION ACTIVITY OF LAP IN PATIENT’S WITH TYPE 2 DIABETES BY USING LEUCINE AMIDE AS SUBSTRATE - Khaleel, Fayhaa M; Mohamad, Tagreed U; Hameed, Areej SH (Al-Nahrain Journal of Science, 2018)
This study was performd on 50 serum specimens of patients with type 2 diabetes, in addition, 50normal specimens were investigated as control group. The activity rate of LAP in patients(560.46 10.504) I.U/L and activity rate of LAP in healthy(10.58 4.39)I.U/L.The results of thestudy reveal that Leucine aminopeptidase (LAP) activity of type 2 diabetes patient s serum shows ahigh signifiacant increase (p < 0.001) compare to healthy subjects. Addition preparation leucineamide as substrate of LAP, identification melting point and spectra by FTIR.